A Prospective Evaluation of Femoral Tunnel Placement for Anatomic Anterior Cruciate Ligament Reconstruction Using 3-Dimensional Magnetic Resonance Imaging. Issue 1 (January 2018) - Hart, Adam; Sivakumaran, Thiru; Burman, Mark; Powell, Tom; Martineau, Paul A.
Background: The recent emphasis on anatomic reconstruction of the anterior cruciate ligament (ACL) is well supported by clinical and biomechanical research. Unfortunately, the location of the native femoral footprint can be difficult to see at the time of surgery, and the accuracy of current techniques to perform anatomic reconstruction is unclear. Purpose: To use 3-dimensional magnetic resonance imaging (3D MRI) to prospectively evaluate patients with torn ACLs before and after reconstruction and thereby assess the accuracy of graft position on the femoral condyle. Study Design: Cohort study; Level of evidence, 3. Methods: Forty-one patients with unilateral ACL tears were recruited into the study. Each patient underwent 3D MRI of both the injured and uninjured knees before surgery. The contralateral (uninjured) knee was used to define the patient's native footprint. Patients then underwent ACL reconstruction, and the injured knee underwent reimaging after surgery. The location and percentage overlap of the reconstructed femoral footprint were compared with the patient's native footprint. Results: The center of the native ACL femoral footprint was a mean 12.0 ± 2.6 mm distal and 9.3 ± 2.2 mm anterior to the apex of the deep cartilage. The position of the reconstructed graft was significantly different, with a mean distance of 10.8 ± 2.2 mm distal ( P = .02) and 8.0 ± 2.3 mm anterior ( P = .01). The mean distance between the center of the graft and the center of the native ACL femoral footprint (error distance) was 3.6 ± 2.6 mm. Comparing error distances among the 4 surgeons demonstrated no significant difference ( P = .10). On average, 67% of the graft overlapped within the native ACL femoral footprint. Conclusion: Despite contemporary techniques and a concerted effort to perform anatomic ACL reconstruction by 4 experienced sports orthopaedic surgeons, the position of the femoral footprint was significantly different between the native and reconstructed ACLs. Furthermore, each surgeon used a different technique, but all had comparable errors in their tunnel placements.